1988
DOI: 10.1111/j.1365-2621.1988.tb07854.x
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Functional Properties of Linseed Protein Products Containing Differing Levels of Mucilage

Abstract: The functionality of two high-mucilage protein concentrates (HMPC) prepared from linseed and linseed expeller cake by extracting and coprecipitating the mucilage with protein was compared with those of a low-mucilage flour (LMF), a protein concentrate (LMPC), and a protein isolate (LMPI) in simple systems. The HMPC samples had better water absorption and emulsifying properties, higher foaming capacity, but lower nitrogen solubility, oil absorption, and foam stability than LMF and LMPC. They also registered hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(40 citation statements)
references
References 25 publications
3
37
0
Order By: Relevance
“…Among CF flours CF I and II B required significantly (p≤0.05) higher water for preparation of dough, probably due to sprouted green gram. Sprouting is known to break the bio-molecules into smaller subunits resulting in more available water binding sites (Dev and Quensil 1988) increasing the requirement of water to make a dough. Fat content of CF biscuits was significantly (p≤0.05) higher than C biscuits which could be due to high fat ingredients like corn flour and roasted peanuts.…”
Section: Resultsmentioning
confidence: 99%
“…Among CF flours CF I and II B required significantly (p≤0.05) higher water for preparation of dough, probably due to sprouted green gram. Sprouting is known to break the bio-molecules into smaller subunits resulting in more available water binding sites (Dev and Quensil 1988) increasing the requirement of water to make a dough. Fat content of CF biscuits was significantly (p≤0.05) higher than C biscuits which could be due to high fat ingredients like corn flour and roasted peanuts.…”
Section: Resultsmentioning
confidence: 99%
“…Protein isolate was prepared from defatted flaxseed meal by alkali extraction that was followed by acid-induced protein precipitation (16). Flaxseed protein isolate was hydrolyzed for 6 h with alcalase according to the modified method of Aluko and Monu (17) at an enzyme/substrate ratio of 1.5:25.…”
Section: Methodsmentioning
confidence: 99%
“…As it is well known that flaxseeds passes through the gut as such and useful nutrients are not absorbed by the body, therefore efforts are being made to remove the hard outer layers of the seeds by using different methods viz., crushing, dehulling, grinding etc. Dehulling removes the hull which results in the elimination most of the mucilage and crude fiber (Dev and Quensel 1988). Dehulled seed contain high level of protein and low carbohydrate content, which makes the flaxseed as potential ingredient for food and feed products (Oomah and Mazza 1997).…”
Section: Dehullingmentioning
confidence: 99%
“…Dry dehulling is also practiced using mechanical methods. Simple process of dry dehulling involves fractionation of ground flaxseeds using graded sieves and air separation method (Dev and Quensel 1988;Smith et al 1946). Method adopted by Smith et al 1946 revealed that adjusting the moisture content of the seed before grinding results in significant improved separation of hull with less contamination of cotyledon fractions.…”
Section: Dehullingmentioning
confidence: 99%